Implementation Of Sustainable Urban Development Based On New Urban Agenda, A Case Of Penang, Malaysia - Behrang, Mohsen (2021)
This research investigates the inclusion of sustainable urban development pillars in Malaysian urban plans and policies; the implementation of SUD; and how the drivers and barriers affect achieving sustainable urban development in Malaysia